STRUCTURE OF TEACHER'S COMPETENCE FOR PRODUCTION OF WEB PAGES FOR ECUCATION - KUBRICKÝ, Jan (Trends in education, 2009)
The paper deals with problems of teacher's competence with a view to particular sphere for education support. It focuses about structure of teacher's competence for production of web pages for education.
Keywords: teacher's competence; ICT; web pages for education.